(untitled) (Spectrum, 2022)
This paper explores different representations of female sexuality portrayed in the poetry of a nineteenth-century American poet, Emily Dickinson (1830-1886) and a twentieth-century Iranian poet, Forough Farrokhzad (1934-1967). Their poetry has been largely characterized by an assertion of female sexuality and its impact on female creativity. Their works particularly highlight the ways male sexuality subjugates female sexuality and formulates an androcentric world of creativity. As their poetry postulates, women’s suppressions and sufferings in their personalsexual- textual world can be attributed to the phallocentric world that consists of a myriad of socio-ethico-cultural regimens. The patriarchal world is shaped and continues to be consolidated by gender differentiations or binaries which exalt men as superior beings in everything and debase women through masculine hegemony. Thus, this paper traces the counter-masculine representations of female sexuality and creativity in the poetry of Dickinson and Farrokhzad. Spectrum, Volume 16, June 2021: 173-194